Clinical Indications for Extubation in Coma Patients with Severe Neurological Craniocerebral Injury with Meta-Analysis. (19th September 2022) - Ma, Huanhuan; Han, Zhixia; He, Wenlong; Liu, Guowei
Abstract : Computer searches of the PubMed, Cochrane Library, and Embase databases for randomized controlled studies on the effects of intensive nutrition on clinical outcomes in patients with severe craniocerebral injury were conducted from the time of database creation to June 11, 2022, along with manual searches of the relevant literature. Two investigators independently screened the literature, extracted data, and evaluated the risk of bias of the included studies before the effect sizes were combined using RevMan 5.3 statistical software provided by the Cochrane Collaboration Network, and publication bias was detected using Stata 12.0 software. Meta-analysis showed that total protein levels were higher in the intensive nutrition group than in the regular nutrition group (WMD = 4.96 g/L (1.57-8.34), P < 0.001 ); IgA levels were significantly higher in the intensive nutrition group than in the regular nutrition group (SMD = 0.79 (0.51-1.07), P < 0.001 ; SMD = 0.98 (0.58-1.38), P < 0.001 ); IgG levels were significantly higher in the fortified group than in the regular group (SMD = 0.98 (0.58-1.38), P < 0.001 ); CD4/CD8 was significantly higher in the fortified patients than in the regular patients with a combined effect size of WMD = 0.33 (0.18-0.48) (P < RR = 0.45 (0.27-0.75), P = 0.002 ). The results show that effective support of early enteral nutrition can reduce the occurrence of gastrointestinal complications in patients, give them a better adaptation process to the gastrointestinal tract, and ensure the degree of tolerance of their gastric mucosa, thus absorbing more nutrition. Fortification significantly reduced the incidence of gastric retention in patients with craniocerebral injury (RR = 0.19 (0.07-0.49), P < 0.001 ). In the subgroup analysis of the three groups, it was shown that, depending on the starting time, the total protein level and IgG level were better in the early nutrition at 24 h than in the late nutrition above 24h and that, depending on the starting dose, the total protein level, IgA, IgG, and CD4/CD8 were better in the intervention at doses above 30 mL/h, using the starting dose of 30 mL/h as the cut-off point. In the subgroup analysis based on different nutrition methods (enteral and parenteral nutrition), IgA levels and the incidence of bloating and diarrhea were better than those of parenteral nutrition in the indicators of enteral nutrition.